Assets and liabilities of drug repositioning - RUPAM GILL; AMBERKAR MOHAN BABU V.; MEENA KUMARI K. (International Journal of Pharma and Bio Sciences, 2016)
Drug discovery is an awfully tenacious job that takes an enormous amount of time, resources, and money, yet yields unsubstantial results. Drug repositioning is a method for "discovering new uses for old drugs." The main objective to repurpose a drug is to extend the application line of an existing drug, thereby narrowing the productivity gap and at the same time allows a swift reach to the market with high chances of revenues. This approach aims at new formulations, dosage, drug combination, delivery system, alternative pathways and targets, orphan diseases. Likewise the de novo drug development, drug repositioning also shares many pros and cons. At one hand, drug repositioning offers relatively less risk-versus-reward ratio; on the other hand, the regulatory authority approval process, intellectual property rights and out-licensing are issues of concern. This review article will particularly focus on the various pros and cons associated with drug repositioning.